A Syntactic Analysis on Noun Phrase Used in English Song By Ed Sheeran Album - Sri Astia Widia Astuti (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
This study entitles “A Syntactic Analysis on Noun Phrase Used in English Song by Ed Sheeran Album”. This study analysis of Noun Phrase by using Jumanto’s theory that indicate in his arrangement. This study focused only on the discussion underlined and coding of types of noun phrase. It was found that there are 118 noun phrase im 93 lyrics from the five selected song in the english song lyrics by Ed Sheeran album. There are 92 premodifier or 78%, 4 post modifier or 3,4%, and 23 premodifier and postmodifier at the same time or 18,6%. The most dominant used of noun phrase in the English song was premodifierthat occurred by 92 data (78%). The finding of the analysis shows that the English Song by Ed Sheeran Album has all types of Noun Phrase. The arrangement by Jumanto’s theory it is easy to provide representation of the noun phrase.